1997
DOI: 10.1046/j.1365-2036.1997.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with cisapride after healing of erosive oesophagitis: a double‐blind placebo‐controlled trial

Abstract: The relapsing nature of re¯ux oesophagitis has been well documented in a number of short-term follow-up studies 1±3 and it is known that re¯ux symptoms persist in the majority of oesophagitis patients at least 10 years after diagnosis. 4 To date the best results for maintenance therapy after healing of oesophagitis have been achieved with proton pump inhibitors, which have been reported to reduce relapse rates at 1 year to 10± 30%. 3,5,6 However, although proton pump inhibitors are now accepted as the most ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Two studies found that cisapride caused a reduction in oesophageal acid exposure 31 , . 32 In contrast, three other studies, in which a larger number of GERD patients were investigated, showed that cisapride had no effect on acid reflux 33 –35 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies found that cisapride caused a reduction in oesophageal acid exposure 31 , . 32 In contrast, three other studies, in which a larger number of GERD patients were investigated, showed that cisapride had no effect on acid reflux 33 –35 …”
Section: Discussionmentioning
confidence: 95%
“…However, this effect was not significant in the supine and in the total 24 h periods, and cisapride did not affect the mean time of exposure of the oesophagus to acid reflux. Previous studies on the effects of an oral dose of cisapride on oesophageal pH in adult GERD patients have yielded conflicting results 31 –35 . Two studies found that cisapride caused a reduction in oesophageal acid exposure 31 , .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the latter was more reproducible in the pivotal US studies led to the rather unusual and restrictive labeling for nocturnal heartburn. Furthermore, other studies examining both the induction of remission 78 and prevention of relapse [79][80][81] showed unimpressive benefits for cisapride as a monotherapy, especially when compared to omeprazole. 81 In children, in contrast to, and despite its advocacy in this patient group, 16 there was no evidence of benefit when all studies were critically evaluated.…”
Section: Gerdmentioning
confidence: 99%
“…It would appear that cisapride has little effect on gut function in normality, but only enhances gastric motor function when a pathological motor dysfunction is present (Brummer et al 1997). For example, in the lower oesophageal sphincter (LOS), cisapride has a normalising action when the sphincter pressure is low (McDougall et al 1997), but has little effect on the LOS when pressures are within the normal range.…”
Section: ) Therapeutic Interventions In the Treatment Of Gastric Ilementioning
confidence: 99%